ANALISIS PERMASALAHAN PEMBELAJARAN DARING PADA SISWA SELAM MASA PANDEMI COVID-19 - sarwati, sarwati; Marhamah, Marhamah; Marzuki, M.; Wazni, Muhammad Khairul; Wahyuni, Muliana (UNIVERSITAS HAMZANWADI, 2021)
Abstract :Online Learning is a learning activity carried out from home which is one of the policies of the government to reduce the spread of the Covid-19 virus that is currently happening in Indonesia. However, online learning is inseparable from the problems that hinder its implementation so that researchers conduct research on online learning problems using qualitative methods. The implementation of Online learning for students at MA NW Penendem is not optimal due to several factors, namely lack of facilities, the role of parents, teachers and schools that are not optimal and low student motivation in implementing online learning. The things that become problems in online learning are quota and singles are not available, parents do not accompany and remind online learning schedules, delivery of unattractive material, survey implementation of online learning activities is not comprehensive, free internet quota cannot be used optimally, students not happy, not enthusiastic, feel difficult and undisciplined in studying Online.